International migration: A panel data analysis of the determinants of bilateral flows - Anna Maria Mayda (Centre for Research & Analysis of Migration (CReAM), Department of Economics, University College London, 2007)
In this paper I empirically investigate the determinants of migration inflows into fourteen OECD countries by country of origin, between 1980 and 1995. I analyze the effect on migration of average income and income dispersion in destination and origin countries. I also examine the impact of geographical, cultural, and demographic factors as well as the role played by changes in destination countries' migration policies. My analysis both delivers estimates consistent with the predictions of the international migration model and generates empirical puzzles.
Keywords: F22; F1; 330; International Migration; Determinants; Push and Pull Factors; Migration Policy